PENINGKATAN KEMAMPUAN MEMBACA DAN HASIL BELAJAR SISWA KELAS VI DENGAN METODE PQRST PADA TEMA SELAMATKAN MAHKLUK HIDUP SUB TEMA LESTARIKAN HEWAN DAN TUMBUHAN DI SD NEGERI 2 TENGGIR KECAMATAN MANGARAN KABUPATEN SITUBONDO TAHUN PELAJARAN 2015/2016 - Dian Aisyatur Ridlo; Aenor Rofek (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
This study is a class action that aims to improve reading skills and student learning outcomes using PQRST on the theme of living creatures to save the sub theme preserve animals and plants (Case study: fourth grade SDN 2 Tenggir Mangaran District of Situbondo in the academic year 2015-2016 ). This research was conducted by 2 cycles, each of which comprises four stages: planning, action, observation and reflection. Based on the results of the discussion can be concluded that the method PQRST (Preview, Question, Read, summarize and Test) can improve reading skills and student learning outcomes. Prior to the act of reading ability of students only achieve 56% increase in the implementation of measures first cycle at 73% and increase the implementation of the second cycle of 93%